LEVELS OF VITAMIN D AND VITAMIN D PATHWAY GENE POLYMORPHISMS IN ADULTS: RESULTS BASED ON RURAL AGRICULTURE WORKERS IN PUNJAB PROVINCE OF PAKISTAN - Hussain, Nadia; Said, Amira SA; Baig, Mirza Rafi (Progress in Nutrition, 2020)
Background and aims: Worldwide low levels of vitamin D (< 30ng/dL) is prevalent and linked to bone disorders, diabetes and coronary heart disease. Deficiency in Vitamin D is a diagnostic challenge in asymptomatic individuals. The present study aimed to assess the environmental and also the genetic determinants affecting vitamin D deficiency in an asymptomatic rural agricultural population sample of Punjab province of Pakistan. Material and method: An interview based questionnaire and blood samples for measuring serum markers were obtained. These include calcium levels, parathyroid hormone and serum 25(OH) vitamin D. DNA was extracted from the blood samples for genotyping. Results: From 510 study participants, 435 (85.2%) individuals had < 30 ng/dL (low) of vitamin D. Males versus females had a unremarkable difference in the status of Vitamin D (61.3% vs 56.2%), (p = 0.134). When calcium levels were compared between the deficiency and insufficiency groups versus the vitamin D sufficiency group, no significant difference was observed (p = 0.526, 0.155 respectively). Consumption of single milk serving every day (250 ml) (p = 0.818) and sunlight exposure every day for more than 30 minutes (p = 0.579) also had non-significant associations with the estimated vitamin D levels. However, oral vitamin D supplementation was significantly associated (p = 0.024) with the vitamin D levels. Eight SNPs were studied and none showed any statistical significant association with observed vitamin D levels. Conclusions: We noted a considerable proportion of asymptomatic individuals from the rural population with low vitamin D levels. There appear to be multifactorial causes of deficiency in vitamin D and this burgeoning health issue requires further investigations.